Jovens estudantes de música na cibercultura musical: facebook e educação musical 2.0 - Bechara, Silvia Regina de Camera Corrêa [UNESP] (2015)
My experiences with young people in the classroom, observing their dynamics in transit in different contexts - online, offline, school, music - awakened in me the curiosity to better understand how to get along these relationshi ps, and in what this implied a Musical Education contemporaneity. Thus, this research deals with the interactions between young music students and music cyberculture in Facebook social media and its implications for the field of music education. It also proposes to unveil the joints of shares linked to the music with the musical training of young music students between 18 and 29 years. Through a field research based on virtual ethnographic resources, data were collected via virtual participant observation Facebook and asynchronous online interviews. The theoretical framework constitutes a mosaic of concepts: musical culture, musical worlds, share, cyberculture, musical cyberculture, postmodernity and Music Education. Interpretation of the data is shown through an art gallery, in which its various wings bring the reflections of the practices of musical cyberculture and Music Education. In this context, students share their emotions, thoughts and opinions and use Facebook extensively to publicize their work. The results show that Facebook used in daily lives does not bring much contribution to the musical education of participating students, but it shows a relevant tool for the construction of musical knowledge from that mediated by an educator